2007
DOI: 10.1111/j.1949-3606.2007.tb00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Disability Course on Prospective Educators' Attitudes Toward Individuals with Mental Retardation

Abstract: Prospective educators who completed a course about social work with disabilities were participants in a study that investigated whether attitudes toward individuals with mental retardation (MR) would be enhanced by the information provided in the course. The quasi-experimental design of the study involved a control group together with a pretest and a posttest, and several demographic and experiential variables. The study used a version of the Mental Retardation Attitude Inventory-Revised that Kandari and Salih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Although there is inconsistency with the studies of Al-Kandari and Salih (2008), Salih and Al-Kandari (2007), and Al-Kandari (2014) conducted on high school and college students in Kuwait, evidence exists that knowing a person with IDD and having a close or casual relationship with them can improve Global Attitudes towards people with IDD, when compared with students who did not know a person with IDD, or had an intimate relationship or only an acquaintanceship with a person with IDD. Evidence was also found to show the positive attitude of high school students towards people with IDD for the Social Distance and Private Rights subscales.…”
Section: Knowing a Person With Idd And Intimacymentioning
confidence: 94%
See 2 more Smart Citations
“…Although there is inconsistency with the studies of Al-Kandari and Salih (2008), Salih and Al-Kandari (2007), and Al-Kandari (2014) conducted on high school and college students in Kuwait, evidence exists that knowing a person with IDD and having a close or casual relationship with them can improve Global Attitudes towards people with IDD, when compared with students who did not know a person with IDD, or had an intimate relationship or only an acquaintanceship with a person with IDD. Evidence was also found to show the positive attitude of high school students towards people with IDD for the Social Distance and Private Rights subscales.…”
Section: Knowing a Person With Idd And Intimacymentioning
confidence: 94%
“…Also, Pettigrew and Troop (2000) stated that 94% of the 203 studies about contact and attitudes indicated an inverse relationship between face-to-face contact and negative attitudes. Although some Eastern studies that were conducted in China (e.g., Siperstein et al, 2011;Wong, 2008), Kuwait (e.g., Salih & Al-Kandari, 2007;Al-Kandari & Salih, 2008), and Japan (e.g., Horner-Johnson et al, 2002) found a small effect of contact between students with and without IDD in changing students' attitudes towards inclusion, other studies (e.g., Chadsey, 2004;Siperstein et al, 2007) suggested that if students have limited opportunities to interact with a peer with IDD in the educational setting, their attitudes towards inclusion will remain negative.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This can make it difficult for the mother to find information, resources, and emotional support from the community. Salih and al‐Kandari () pointed out that the lack of public knowledge about disabilities causes many people to rely on negative stereotypes. The exclusion of people with disabilities from positive public roles means many people are never exposed to positive examples of individuals with disabilities.…”
Section: Parenting Stressmentioning
confidence: 99%
“…In addition, Salih and Kandari (2007) suggest that parents may find the challenging task of caregiving more difficult when there are negative attitudes toward the child with DD in one's immediate environment. A parent who is employed, for example, may not be able to find a good babysitter for the child at certain times during the day because of the negative perception of others toward a child with a disability.…”
Section: Introductionmentioning
confidence: 96%